INTERNATIONAL MARKETING AND ITS IMPACT ON ENTREPRENEURSHIP-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT RASHID BANK, KARBALA BRANCH - Assistant Lecturer: Mayasah Nadhim Azeez Mohammed (Scholars Digest Publishing, 2025)
The aim of the research is to identify the nature of international marketing and its basic dimensions, in addition to identifying the level of work of both international marketing and entrepreneurship in the Iraqi Rasheed Bank, as well as identifying the personality and impact of international marketing, its dimensions, and service leadership for the Iraqi Rasheed Bank. Marketing plays an important role in the success of any sports project. It is the driving force that helps entrepreneurs sell their products or services effectively, connect with their target audience, Without a well-defined marketing strategy, even the most innovative and promising ideas can fail to capture the market's attention. The research used a simple random sampling method to select the study sample, which was represented by employees of Al-Rasheed Bank, Karbala branch, and its size reached 45 individuals. The results of the research showed that Al-Rasheed Bank of Iraq applied the entrepreneurship strategy. The results of the research indicated that Al-Rasheed Bank of Iraq applied the entrepreneurship strategy, so it came in the ranking, and the most important personal characteristics that must be present in an entrepreneur were commitment to work. The results of the research also showed the impact of international marketing on entrepreneurship represented by evaluating Market potential and economic indicators.
Keywords: International marketing – entrepreneurship- Marketing strategy-Global Digital Marketing